Toleransi pada Anak: Bagaimana Peran Keluarga dan Sekolah? - Pranawati, Santy Yanuar; Hidayah, Bidayatul (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Promoting tolerance is vital to reduce prejudice and discrimination towards outgroups. Therefore, family and school are essential in encouraging children's tolerance as an immediate environment. This literature review provides an overview of the role of family and school in promoting tolerance in children to reduce prejudice toward outgroups. We used the standard systematic literature review method employing a manual search of articles through the keywords, i.e., children, family, school, prejudice, and tolerance. The data source was obtained online using ProQuest, Taylor & Francis (Social Sciences & Humanities Subject), and Ebscohost. There are 41 articles included in quality appraisal using the qualitative assessment. We concluded that family and school, as an immediate environment of child development, are essential in promoting tolerance to prevent negative prejudice towards outgroups. This literature review may have implications, especially for the family and school environment, in enhancing children's tolerant attitude as early as possible over several activities to increase knowledge about their outgroups.